Customs inspection of individuals: between human rights and national security interests: The United Arab Emirates (as a case study) - Jassem Mohammed Alnuaimi (International Journal of Law Research and Studies, 2025)
The research aims to clarify the conditions and terms stipulated in international agreements and national legislation in the state’s exercise of its right to customs inspection of persons and the legal tools that the state can use to ensure that customs inspection of persons is consistent with international human rights standards, and to clarify the impact of national and international legislation in the field of human rights on customs inspection practices and the most important challenges, and to clarify international experiences and practices in this field. The research adopted the descriptive approach (content analysis) in its inductive and analytical manner. Among the results reached is that customs inspection is an administrative and security procedure used by countries to verify compliance with customs laws and to protect national security interests from threats and the importance of conducting it in a manner that respects human rights and individual dignity. Among the most prominent recommendations is the importance of working to establish rules, controls and obligations that regulate the use of modern technologies and smart devices in customs inspection and working to establish behavioral rules for customs judicial control officers when practicing their job duties.